2015
DOI: 10.1017/neu.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

No effect of escitalopram versus placebo on brain-derived neurotrophic factor in healthy individuals: a randomised trial

Abstract: The results of this randomised trial suggest that escitalopram 10 mg has no effect on peripheral BDNF levels in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…There is evidence that both serum and plasma BDNF concentrations are decreased in patients with MDD (Piccinni et al 2008) and antidepressants are reported to normalize these abnormalities (Aydemir et al 2006;Piccinni et al 2008;Sen et al 2008). Some research supports ((Sen et al 2008) the use of increased peripheral levels of BDNF as a screening tool for novel antidepressant agents, while other research opposes ( (Brunoni et al 2014;Buttenschøn et al 2015;Deuschle et al 2013;Knorr et al 2015) this proposition. Antidepressants influence both peripheral BDNF and platelet 5-HT concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that both serum and plasma BDNF concentrations are decreased in patients with MDD (Piccinni et al 2008) and antidepressants are reported to normalize these abnormalities (Aydemir et al 2006;Piccinni et al 2008;Sen et al 2008). Some research supports ((Sen et al 2008) the use of increased peripheral levels of BDNF as a screening tool for novel antidepressant agents, while other research opposes ( (Brunoni et al 2014;Buttenschøn et al 2015;Deuschle et al 2013;Knorr et al 2015) this proposition. Antidepressants influence both peripheral BDNF and platelet 5-HT concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…G. Simmons & Allen, 2011; J. G. Simmons, Nathan, Berger, & Allen, 2011; Ježová & Duncko, 2002; Kellner et al, 2008, 2009; Knorr, Koefoed, Gluud, et al, 2016; Knorr, Koefoed, Soendergaard, et al, 2016; Knorr, Vinberg, Gade, et al, 2011; Knorr, Vinberg, Gether, et al, 2012; Knorr, Vinberg, Hansen, et al, 2011; Knorr, Vinberg, Mortensen, et al, 2012; Knutson et al, 1998; Kotzailias, Marker, & Jilma, 2004; Kraus et al, 2014; Loubinoux et al, 2005; Macoveanu, Fisher, et al, 2014; Macoveanu, Knorr, et al, 2014; Madeo et al, 2008; Matthews et al, 2010; McCabe & Mishor, 2011; McCabe, Mishor, Cowen, & Harmer, 2010; M. Taylor et al, 2008; M.…”
Section: Resultsmentioning
confidence: 99%
“…In two trials of 16 and 25 participants, respectively, the gender distribution was not reported (Chial et al, 2003; Pohl et al, 2003). Seven of the 51 trials took account of potential age effects on the outcome or reported separate analyses of age in relation to outcome (Bui et al, 2013; Carpenter et al, 2011; Haahr et al, 2014; Kellner et al, 2009; Knorr, Koefoed, Gluud, et al, 2016; Knorr, Koefoed, Soendergaard, et al, 2016; Knorr, Vinberg, Gade, et al, 2011; Knorr, Vinberg, Gether, et al, 2012; Knorr, Vinberg, Hansen, et al, 2011; Knorr, Vinberg, Mortensen, et al, 2012; Kraus et al, 2014; Talley et al, 2005). Knorr, Vinberg, Hansen, et al, 2011 found a statistically significant interaction between the outcome and age as the only trial out of the seven.…”
Section: Resultsmentioning
confidence: 99%
“…One proposed mechanism for the effect of SSRIs is an upregulation of CREB mRNA in the hippocampus and subsequently an increased expression of BDNF and TrkB [36]. Knorr et al have been, until now, the only group to investigate the effect of chronic escitalopram administration on whole blood BDNF levels in healthy subjects [20]. They reported a significant negative correlation between citalopram and whole blood BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Escitalopram possesses an adequate tolerability and dose-dependent mild and temporary adverse events [19]. Previous studies had already shown its tolerability in healthy volunteers when administered longitudinally [20]. Plasma levels for escitalopram can be detected from citalopram plasma levels since the latter contains both, S-and R-citalopram.…”
Section: Study Drug Administration and Assessment Of Ssri Plasma Levelsmentioning
confidence: 99%